Challenges facing the governance of Islamic banks in the presence of the Shari'a Supervisory Board (Journal of Human Sciences, 2018)
This paper sheds light on some of the challenges facing the management of Islamic banks in light of the existence of the Sharia Supervisory Board in terms of its compliance with the principles of good governance. Unified legitimacy, as well as the combination of different authorities and conflicting interests, which raised the concerns of many researchers and observers on issues related to confidentiality, transparency and competition. In addition, there are some controversy on some issues related to the independence of members of the Shariah Supervisory Board Bank.